Peningkatan Mutu Sarana Pendidikan Melalui Pengembangan Self Access Library For English Students (SALE) - Hidayati, Fithriyah Nurul; Fatmawati, Nor Laili (LPM IHDN Denpasar, 2020)
The research and development of Self Access Library for English Studets (SALE) is aimed at increasing the quality of educational tools as mandated by Permenristekdikti RI No. 44 2015 and its change Permenristekdikti RI No. 50Â 2018 about National Standard of Higher Education (SN Dikti). It is conducted based on the need of students of PBI IAIN Surakarta for comprehensive, accurate, easily accessible and inexpensive learning sources. Thus, SALE is initiated as an online library providing 126 English e-books classified based on the syllabus of PBI, covering the topics on English education, linguistics ang literature so the students can find appropriate learning sources easily. SALE also gives the students connections to some experts so they can meet virtual consultants or discussion partners to confirm their reading comprehension on the issues concerned. The research and development include some steps; observing potential problems, collecting data, designing SALE, validating the product by experts, first revision, small group trial, second revision, user trial, packaging, and final product. The score of validation by the experts and small group trial shows that SALE is categorized very good and eligible. It means SALE is ready to be an alternative learning source provider with qualified long distance service. The use of SALE by the students causes the improvement on studentsâ€™ tasks quality as the result of an easy access to some important references appropriate with their majors. Therefore, SALE has become an evidence of the efforts to improve the quality of educational toools at IAIN Surakarta, particularly at PBI department